Metabolic Therapy for Temporal Lobe Epilepsy in a Dish: Investigating Mechanisms of Ketogenic Diet using Electrophysiological Recordings in Hippocampal Slices - Kawamura, Masahito Jr.; Ruskin, David N.; Masino, Susan A. (Frontiers in Molecular Neuroscience, 2016)
The hippocampus is prone to epileptic seizures and is a key brain region and experimental platform for investigating mechanisms associated with the abnormal neuronal excitability that characterizes a seizure. Accordingly, the hippocampal slice is a common in vitro model to study treatments that may prevent or reduce seizure activity. The ketogenic diet is a metabolic therapy used to treat epilepsy in adults and children for nearly 100 years; it can reduce or eliminate even severe or refractory seizures. New insights into its underlying mechanisms have been revealed by diverse types of electrophysiological recordings in hippocampal slices. Here we review these reports and their relevant mechanistic findings. We acknowledge that a major difficulty in using hippocampal slices is the inability to reproduce precisely the in vivo condition of ketogenic diet feeding in any in vitro preparation, and progress has been made in this in vivo/in vitro transition. Thus far at least three different approaches are reported to reproduce relevant diet effects in the hippocampal slices: (1) direct application of ketone bodies, (2) mimicking the ketogenic diet condition during a whole-cell patch-clamp technique, and (3) reduced glucose incubation of hippocampal slices from ketogenic diet–fed animals. Significant results have been found with each of these methods and provide options for further study into short- and long-term mechanisms including ATP-sensitive potassium channels, vesicular glutamate transporter, pannexin channels and adenosine receptors underlying ketogenic diet and other forms of metabolic therapy.